Polymorphism of the 5-HT2A receptor gene: Association with stress-related indices in healthy middle-aged adults - Fiocco, Alexandra J.; Joober, Ridha; Poirier, Judes; Lupien, Sonia (Frontiers in Behavioral Neuroscience, 2007)
Past research has concentrated on the stress system and personality in order to explain the variance found in cognitive performance in old age. A growing body of research is starting to focus on genetic polymorphism as an individual difference factor to explain the observed heterogeneity in cognitive function. While the functional mechanism is still under investigation, polymorphism of the 5-HT2A receptor gene (-1438A/G) has been linked to certain behavioral and physiological outcomes, including cortisol secretion, the expression of certain personality traits, and memory performance. It was the goal of the present study to investigate the association between the -1438A/G polymorphism and stress hormone secretion, stress-related psychological measures, and cognitive performance in a group of adults between the ages of 50 and 65. To examine these associations, 101 middle-aged adults were recruited, completed a battery of psychological questionnaires and were administered a battery of cognitive tasks that assess frontal lobe and hippocampal function. Basal and stress-reactive salivary cortisol levels were collected, at home and in the laboratory. Analyses on psychological measures showed that participants with the GG genotype reported significantly higher levels of neuroticism compared to the AG group and higher levels of depression and more emotion-based coping strategies compared to both the AG and AA group. In terms of cortisol secretion, the AA genotype was related to a significantly higher awakening cortisol response (ACR) compared to the AG and GG group and the GG genotype group displayed a greater increase in cortisol secretion following a psychosocial stressor compared to the two other groups. On measures of cognitive performance, the AA genotype group performed significantly better on a test of declarative memory and selective attention compared to the other two groups. Together, these results suggest that carriers of the GG genotype are more susceptible to low mood and display a greater potential for an overactive stress system, which may influence cognitive function in later years.